2009
DOI: 10.1111/j.1442-2050.2009.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative weight loss and body mass index on postoperative outcome in patients with esophagogastric carcinoma

Abstract: Studies have shown that weight loss is associated with adverse outcomes in all treatment modalities for esophagogastric carcinoma. Because of the increased prevalence of obesity and the effectiveness of perioperative nutrition, a number of patients are now obese or have normal body mass index (BMI) at the time of treatment. We investigated the relationship between weight loss, BMI, and outcome of surgery for patients with esophagogastric carcinoma. Data were collected over a 38-month period for all patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 22 publications
1
34
0
1
Order By: Relevance
“…A few reports that specifically focused on BMI suggested that pretreatment BMI was not associated with differential outcome with regard to OS or DFS. [12][13][14] However, the largest study to date is by Trivers et al 17 18 demonstrated that a BMI of >18 kg/m 2 was one of the independent prognostic factors in 105 patients treated with definitive chemoradiotherapy (P ¼ .003). However, in this study, the cutpoint for BMI was nontraditional and the sample size was small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few reports that specifically focused on BMI suggested that pretreatment BMI was not associated with differential outcome with regard to OS or DFS. [12][13][14] However, the largest study to date is by Trivers et al 17 18 demonstrated that a BMI of >18 kg/m 2 was one of the independent prognostic factors in 105 patients treated with definitive chemoradiotherapy (P ¼ .003). However, in this study, the cutpoint for BMI was nontraditional and the sample size was small.…”
Section: Discussionmentioning
confidence: 99%
“…8 High BMI is a risk factor for gastroesophageal reflux disease (GERD) and, consequently, for EAC. [9][10][11] Several studies have reported that high BMI was not associated with improved or reduced overall survival (OS) after esophagectomy, [12][13][14] although increased postoperative morbidity, such as respiratory complications, anastomotic leaks, and length of hospital stay, have been associated with high BMI in patients with gastroesophageal cancer who are undergoing surgery. 14,15 Many of these studies included small number of patients, in whom adjunctive therapy (preoperative chemotherapy and/or radiotherapy) was used.…”
mentioning
confidence: 99%
“…serum albumin, transferrin, and nitrogen balance studies; (iii) subjective global assessment (SGA) based on medical history and physical examination; patient-generated SGA (PG-SGA) adapted from the SGA specifically for cancer patients; (iv) the malnutrition screening tool (MST), considered the quickest and most simple tool for nutritional screening by the American Society for Parenteral and Enteral Nutrition (ASPEN); (v) Nutritional Risk Screening 2002 (NRS-2002), designed to detect malnutrition and the risk of developing malnutrition in the hospital setting as recommended by the European Society for Clinical Nutrition and Metabolism (ESPEN) [10], and (vi) the Malnutrition Universal Screening Tool (MUST), developed by the British Association for Parenteral and Enteral Nutrition, devised for application in all adult patients across all health care settings [1]. Many other nutritional parameters, including the Prognostic Nutritional Index, the Nutritional Risk Index, the Nutritional Screening Tool, the Maastricht Index, the Instant Nutrition Assessment, and the Mini Nutritional Assessment, have also been used to attempt to risk stratify patients [3,11,12]. The utility of these nutritional screening tools has been evaluated by their ability to predict relevant clinical outcomes, such as complications, treatment response, survival, hospital length of stay (LOS), and higher costs of health care [4,9,13].…”
Section: Introductionmentioning
confidence: 99%
“…Low body mass index and anemia, as in previous studies, are likely to reflect the presence of general poor health or a more advanced stage of preexisting malignancy status. 19 -22 Low body mass index has been described as a marker of patients who are more likely to have advanced disease including esophageal, 20 gastric, 21 and lung 22 cancers. Anemia has also been shown prospectively to be associated with increased risk for perioperative infection and adverse outcome in surgical patients.…”
mentioning
confidence: 99%